Management of surface and spring water for rice cultivation as climate adaptation in dry land - Anshori Arif; Suswatiningsih Tri Endar (BIO Web of Conferences)
Dry land is characterized by the main problem of water shortage. In karst areas, this problem can be reduced by the presence of springs. This research aims to examine the use of rainfall, surface flow and spring water to support rice planting in the second growing season as a form of adaptation to climatic conditions of dry land in karst areas. The research was carried out on dry land in the Gunungsewu karst area, Gunungkidul D.I. Yogyakarta Indonesia. The research used observation methods, farmer interviews and rice planting trials. The research results show that farmers have managed rainfall, surface flow and spring water for agricultural and household. Utilization of water resources for rice cultivation in the second growing season produced of 6.800 ton ha-1, with income of IDR23,290,000 ha-1. Additional results in the form of straw biomass amounted of 7.232 ton ha-1. Rice requires a lot of water, so water management must based on the soil and water conservation principles, to be sustainable.